Trois bicentenaires : Hume, Condillac, Smith. Adam Smith entre le marginalisme et le marxisme - Pelletier, Gérard-R. (L'Actualité économique, 1977)
AbstractIt is not easy to understand why, and how, orthodox economists who do not believe either in the labor-theory or in the cost-theory of value, continue to favor Adam Smith's Wealth of Nations, but forget such economists as Condillac, whose value theory is nearer to theirs and whose bicentenary we also commemorate.Adam Smith, it is submitted, is still interesting but for reasons far enough from orthodox economic theory. Smith is in fact, according to some recent interpretations, more of a welfare economist, concerned with moral values, than a partial analysis economist: his theory of value derives from ethical considerations following Hume and keeps its normative flavor throughout instead of being solely a tentative explanation of prices. Some apparently contradictory assertions about value could thus be reconciled in a unifying theory, as explained by such authors as Lindgren (1973) or Rieseman (1976).If it is possible to reconcile many apparently contradictory views in Adam Smith's works, thanks to a more holistic approach, it is suggested that a similar approach could be applied to a more controversial economist, Karl Marx, whose career may be compared to that of Smith in many respects.